Integrative proteomics and metabolomics approach to elucidate the antimicrobial effect of simvastatin on Escherichia coli. (13th June 2021) - Kocak, Engin; Nemutlu, Emirhan; Kır, Sedef; Sagıroglu, Meral; Özkul, Ceren
Abstract: Globally, simvastatin is one of the most commonly used statin drugs. Its antimicrobial properties have been investigated against various pathogens. However, its effect on biological processes in bacteria has been unclear. This study focused on altered biological and metabolic processes at protein and metabolite levels induced by simvastatin. MS‐based proteomics and metabolomics were used to investigate the altered proteins and metabolites between experimental groups. Proteomics results showed that simvastatin induced various antimicrobial targets such as chaperon protein DnaK and cell division protein FtsZ. Metabolomics results revealed phenotypic changes in cells under simvastatin stress. Integrated proteomics and metabolomics result indicated that various metabolic processes were altered to adapt to stress conditions. Energy metabolism (glycolysis, tricarboxylic acid cycle, etc.), amino acid synthesis and ribosomal proteins, and purine and pyrimidine synthesis were induced by the effect of simvastatin. This study will contribute to the understanding of antimicrobial properties of statin drugs.